Redox- and pH-responsive fluorescent carbon nanoparticles-MnO2-based FRET system for tumor-targeted drug delivery in vivo and in vitro - Choi, Cheong A; Lee, Jung Eun; Mazrad, Zihnil Adha Islamy; In, Insik; Jeong, Ji Hoon; Park, Sung Young (Journal of industrial and engineering chemistry (Seoul, Korea), 2018)
[Display omitted] •The cancer targeted biosensor showed with redox/pH controllable PTX delivery system guided fluorescent on/off behavior.•The system generates fluorescent off-on system in response to high intracellular GSH concentration and drug release.•The MnO2/PTX-loaded C-FNP can effectively reduce the side effects In vitro and In vivo of cancer cell.•The formulation showed an selective cellular uptake of malignant KB cells suggesting a potential for targeting. The carbonized boronic acid-conjugated fluorescent carbon nanoparticles (FNPs) were crosslinked with carbonized dopamine-conjugated hyaluronic acid (HA) via the diol boronic acid-linked catechol groups [C-FNP] as extracellular targeting ligands and pH responsiveness. Into that C-FNP, the redox-responsive MnO2 nanosheets were loaded to demonstrate quenching effect, which recovered after glutathione (GSH) treatment. The MnO2-loaded C-FNP showed excellent stability and tumor-targeting ability guided to the localized tumor using “on–off” fluorescent switch. Furthermore, paclitaxel (PTX) inside the MnO2-loaded C-FNP performed in vitro and in vivo bioimaging and chemotherapeutic activities analyzed towards cancer and non-cancerous cells.